2016
DOI: 10.1111/sms.12679
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical significance of premature ventricular beats in the athlete

Abstract: Adolescents and adults with cardiovascular disease who are engaged in sports activity have an increased risk of sudden cardiac death (SCD) that is three times greater than that of their non-athletic counterparts. Sport acts as a trigger for cardiac arrest in the presence of underlying cardiovascular diseases predisposing to life-threatening ventricular arrhythmias. Frequent and complex premature ventricular beats (PVBs) detected during the cardiovascular screening of the athletic population may be a sign of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 65 publications
2
27
0
3
Order By: Relevance
“…Our results are in keeping with those of previous studies suggesting that frequent isolated PVBs in young athletes most commonly show infundibular or fascicular morphologic features, which denote benign arrhythmias caused by automatic foci in the absence of a pathologic myocardial substrate that are usually suppressed by exercise 12, 14. Indeed, using 12‐lead electrocardiographic monitoring, we found that all athletes with >500 PVBs/24 hours had either an infundibular or fascicular morphologic feature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in keeping with those of previous studies suggesting that frequent isolated PVBs in young athletes most commonly show infundibular or fascicular morphologic features, which denote benign arrhythmias caused by automatic foci in the absence of a pathologic myocardial substrate that are usually suppressed by exercise 12, 14. Indeed, using 12‐lead electrocardiographic monitoring, we found that all athletes with >500 PVBs/24 hours had either an infundibular or fascicular morphologic feature.…”
Section: Discussionsupporting
confidence: 92%
“…The PVB morphologic features were classified as left bundle branch block like (LBBB) if the ectopic QRS complex was predominantly negative in lead V1 or right bundle branch block like (RBBB) if the ectopic QRS complex was predominantly positive or isodiphasic in lead V1. PVBs with a LBBB/inferior axis (positive QRS complex in aVF and negative QRS complex in V1 and aVL) configuration were considered of ventricular outflow tract origin; PVBs with a QRS duration ≤130 ms resembling a typical RBBB/left or right axis deviation were considered of fascicular origin 12, 14. PVBs with ≥2 morphologic features that accounted for ≥10% of all PVBs were classified as polymorphic.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Currently, anterior TWI is a major criterion for the diagnosis of AC. 14 [15][16][17][18] Calore et al compared the ECG pattern in 80 healthy athletes with anterior TWI with 95 patients affected by HCM and 58 patients by AC. 10 In this study, J-point elevation <1 mm in the anterior leads F I G U R E 1 Electrocardiogram of a 24-year-old female tennis player with T-wave inversion from V1 to V4 at the preparticipation evaluation.…”
Section: Anterior Twimentioning
confidence: 99%
“…Acute and long-term mortality in patients with viral myocarditis is higher in part due to sudden cardiac deaths caused by ventricular arrhythmias [18,19], and there is evidence of QT prolongation in patients with acute myocarditis [11,12]. Some investigations of the prognostic significance of ventricular arrhythmia during exercise have assumed that PVCs are benign [20,21] whereas others detected an association between PVCs and increased risk of cardiovascular or all-cause mortality rates [5,[22][23][24]. In general, those studies examining patients with exercise-associated PVCs did not differentiate between the presence or high probability of coronary artery disease or other underlying cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%